Hubungan Pengetahuan Gizi Dan Body Image Dengan Status Gizi Remaja Putri Pada Masa Pandemi Covid-19 - wijayanti, wijayanti; Puspita Dewi, Wiwik (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) ITS PKU Muhammadiyah Surakarta, 2022)
BPS in 2020 recorded the age group of 10-19 in 2020 for female 21,562 per 100,000. This period is the most critical period that must be considered for nutritional intake because it is vulnerable to nutritional deficiencies. Factors that affect nutrition are body image and lack of nutritional knowledge. The incidence of Corona Virus infection, 10% was occured in patients younger than 39 years. The purpose of the study was to determine the correlation of nutritional knowledge and body image with the nutritional status of adolescent girls during the Covid-19 pandemic. This type of survey research was carried out with a cross sectional approach. The study was carried out at ITS PKU Muhammadiyah Surakarta in January–July 2021. The sample of this research was 30 people with the criteria of ITS PKU Muhammadiyah Surakarta students aged 17-20 years (purposive sampling). Statistical tests were carried out univariate, bivariate, and multivariate. The results of the study 1). There is a positive and significant correlation between adolescent knowledge about nutrition in the Covid-19 pandemic and the nutritional status of adolescent girls (r-count 0.591, Alpha 0.0012) 2) There is a positive and significant correlation between body image and nutritional status of adolescent girls (r-count 0.583, Alpha 0.0013 3). There is a positive and significant correlation between adolescent knowledge about nutrition in the Covid-19 pandemic and body image and nutritional status of adolescent girls (r-count 0.663 and F-count 10.595)